Relicários da paisagem pastoril: uma geografia do Pampa remanescente no Brasil - Monteblanco, Felipe Leindecker (2021)
This thesis analyzed the dynamics of the pastoral landscape remaining from the processes of suppression of Pampa in its relationship with the life that animates it, dialoguing with social subjects who interact with it. The research was carried out between 2017 and 2021, focusing on the high hydrographic basin of the Quaraí River, which is one of the last strongholds in the Brazilian portion of the Pampa to sustain a significant portion of the so-called “natural” areas of the biome. We seek to understand the social and geographic conditions that make this zone resistant to the advancement of the technical soy system underway in the regional surroundings - today the main cause of suppression of the Pampa Biome - analyzing to what extent this contingency allows or not the reproduction of old characteristics of this geographical environment. The theoretical ballast was the understanding of geographic space while content-forms, inseparable materiality from the human actions and representations that move it. This understanding follows our initial presumption that the patches of the remaining Pampa Biome presuppose patches also of systems of practices or actions, content, to some extent. The research was from a qualitative aspect, analytically operationalizing the concept of landscape while a conceptual focus. Two are the groups of finding in this research: the first, on the scale of the Brazilian Pampa and the Southwest of Rio Grande do Sul, it is the result of retrospective geography, based, above all, on bibliographical and documentary research. Through this exercise, we see the historically constructed face of the Pampa: the pastoral landscape, an agrarian landscape. A work with a modern-colonial origin, but which, because it was founded on extensiveness, was labeled as "excessively surrendered to nature", "archaic" or "pre-capitalist". Predestined, according to these exotic modern eyes, to an agricultural destiny as a passport to progress, this centuries-old landscape is now rapidly succumbing to the advance of soy. Remainders, confined in geographies that are refractory to hegemonic uses, which, on the other hand, see the growth of forms of valorization of the diverse and the singular, in the wake of the very after-effects left by productivism and the globalizing massification processes, which translates into the possibility of converting their former marginality into a paradoxical virtue. The second finding group, this on the scale of the spot of remnants concentrated in the Alto Quaraí, is the result of a geography of the present, based basically on fieldwork, with a cross between landscape observation and semi-structured interviews-interlocutions. We visualize, thereby, a reliquary area, whose relics it holds are the very landscape and the Pampas pastoral life that is reproduced there between inertias, transitions and even threats, under the "protection" exercised by the very edaphoclimatic and/or geomorphological conditions of these domains of the superficial basalt soils and/or the minority window of soils of sandstone origin, added, still, to the weight exerted by the reproduction of a certain local historical and cultural reticence to agriculture. We also observe that these same geographic conditioning factors, which generate a buffer effect to the entrance of the crops, make up, on the other hand, the singularities of raising cattle on the "stones" or "sands", which beyond the cultural value they represent, make the Alto Quaraí a true sheep terroir and an area of excellent aptitude for bovine breeding.